2008
DOI: 10.1016/j.matlet.2007.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic properties of ultrathin rf-sputtered Teflon films coated etched aluminum surfaces

Abstract: Superhydrophobicity has been demonstrated on ultrathin rf-sputtered Teflon coated etched aluminum surfaces. The etching of aluminum surfaces has been performed using dilute hydrochloric acid. An optimized etching time of 2.5 min is found to be essential, before Teflon coating, to obtain a highest water contact angle of 164 ± 3° with a lowest contact angle hysteresis of 2.5 ± 1.5°, with the water drops simply rolling off these surfaces with even the slightest inclination of the sample. The presence of − CF3 rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 30 publications
3
113
2
Order By: Relevance
“…There are two main approaches to generate superhydrophobic surfaces: (i) creation of a rough surface from low surface energy materials and (ii) creation of a rough surface followed by a low surface energy material coating step. Many methods have been developed so far to promote surface roughness, including sol-gel, plasma treatment, electrodeposition, anodisation, hot-water immersion, template method, chemical treatment and lithography [13][14][15][16][17][18][19][20]. Anodic aluminum oxide has been proposed as a suitable industrial process for use in the burgeoning field of nanotechnology [21] for developing nano-pore structure films with advantage of improvement of corrosion and wear resistance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are two main approaches to generate superhydrophobic surfaces: (i) creation of a rough surface from low surface energy materials and (ii) creation of a rough surface followed by a low surface energy material coating step. Many methods have been developed so far to promote surface roughness, including sol-gel, plasma treatment, electrodeposition, anodisation, hot-water immersion, template method, chemical treatment and lithography [13][14][15][16][17][18][19][20]. Anodic aluminum oxide has been proposed as a suitable industrial process for use in the burgeoning field of nanotechnology [21] for developing nano-pore structure films with advantage of improvement of corrosion and wear resistance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The micro-nanoroughness on the Al surfaces were created by chemically etching the Al surfaces using dilute hydrochloric acid (HCl). A detailed procedure aluminum etching by HCl is described in our previous work [15]. The surface chemical compositional analyses were performed by X-ray photoelectron spectroscopy (XPS) (VGESCALAB 220iXL).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, our group has been extensively working on the superhydrophobic coatings for its applications in the areas where reduction of ice adhesion is of importance [13], [14], [15], [16], [17], [18] and [19]. The above works are fundamentally based on two step process where initially a rough pattern was created and the rough surface either passivated with fluoroalkylsilane [17] or stearic acid molecules [13], [17], [18] and [19] or coated with rf-sputtered Teflon [15]. Very recently, we have demonstrated that rf-sputtered Teflon coated etched aluminum surfaces are highly superhydrophobic [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This property is related to the special multi-scale nano/microsurface structures and this correlation is widely known as the lotus effect [6,[11][12][13]. In recent years, many technologies including electrochemical deposition [14][15][16], chemical [17][18][19][20][21][22] and plasma etching [23][24][25], electrospinning [26][27][28], and lithograph [29,30] are utilized to fabricate superhydrophobic surface by mimicking the lotus surface structure.…”
Section: Introductionmentioning
confidence: 99%